Cell Receptor and Cofactor Interactions of the Contact Activation System and Factor XI - Pathak, Monika; Kaira, Bubacarr Gibril; Slater, Alexandre; Emsley, Jonas (Frontiers in Medicine, 2018)
The contact activation system (CAS) or contact pathway is central to the crosstalk between coagulation and inflammation and contributes to diverse disorders affecting the cardiovascular system. CAS initiation contributes to thrombosis but is not required for hemostasis and can trigger plasma coagulation via the intrinsic pathway [through factor XI (FXI)] and inflammation via bradykinin release. Activation of factor XII (FXII) is the principal starting point for the cascade of proteolytic cleavages involving FXI, prekallikrein (PK), and cofactor high molecular weight kininogen (HK) but the precise location and cell receptor interactions controlling these reactions remains unclear. FXII, PK, FXI, and HK utilize key protein domains to mediate binding interactions to cognate cell receptors and diverse ligands, which regulates protease activation. The assembly of contact factors has been demonstrated on the cell membranes of a variety of cell types and microorganisms. The cooperation between the contact factors and endothelial cells, platelets, and leukocytes contributes to pathways driving thrombosis yet the basis of these interactions and the relationship with activation of the contact factors remains undefined. This review focuses on cell receptor interactions of contact proteins and FXI to develop a cell-based model for the regulation of contact activation.